The Role of AI in Targeting and Segmentation: A New Era for Marketing Professionals in the Real Estate Sector: Role of AI in Targeting and Segmentation (Academic Journal of International University of Erbil, 2025)
This study investigates the role of Artificial Intelligence (AI) in targeting and segmentation in the real estate sector in Iraqi Kurdistan. Rapid technological advancements and AI usage in different sectors around the world brought researchers' attention to exploring AI's impact on customers' experiences and marketing professionals' willingness and readiness to leverage this technological development. To quantify their willingness and readiness, as well as whether AI influences the effectiveness of targeting and segmentation strategy, this research uses quantitative methods. Means, regression, and correlation analysis are used to investigate the relationship and impact between dependent and independent variables. Moreover, the survey includes both close-ended questions with open-ended questions. Open-ended items give researchers a chance to dive deeper into qualitative insights from respondents. This paper provides mixed results. Even though marketing professionals see AI as a useful tool in segmentation practices, their responses did not match their perception; thus, statistically, the findings were not significant. In addition, the findings reveal that AI has a positive relationship with segmentation strategies despite challenges such as data quality, lack of infrastructure, and issues related to system integration. More research on other sectors, particularly on human resources readiness and operational challenges, is needed.